2022
DOI: 10.1186/s40510-022-00448-x
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional cephalometric outcome predictability of virtual orthodontic-surgical planning in surgery-first approach

Abstract: Objectives The aim of this study is to introduce a novel 3D cephalometric analysis (3DCA) and to validate its use in evaluating the reproducibility of virtual orthodontic-surgical planning (VOSP) in surgery-first approach (SF) comparing VOSP and post-operative outcome (PostOp). Methods The cohort of nineteen patients underwent bimaxillary orthognathic surgery following the VOSP designed in SimPlant O&O software by processing cone-beam computed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The surgical achievability of anterior/posterior translation has always been one of the least accurate surgical movement in orthognathic surgery among cleft and non-cleft patients [ 8 , 15 , 16 ]. Many studies reported that a larger maxillary advancement is correlated with more surgical inaccuracy.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical achievability of anterior/posterior translation has always been one of the least accurate surgical movement in orthognathic surgery among cleft and non-cleft patients [ 8 , 15 , 16 ]. Many studies reported that a larger maxillary advancement is correlated with more surgical inaccuracy.…”
Section: Discussionmentioning
confidence: 99%